2007
DOI: 10.1108/17466660200700004
|View full text |Cite
|
Sign up to set email alerts
|

Using an assessment framework: outcomes from a pilot study

Abstract: This article reports on the evaluation of a pilot project which tested the utility of a framework for the Assessment of Vulnerable Children and their Families in five health board (local authority) areas in the Republic of Ireland. The framework had been developed following a consultancy process with practitioners and managers from a number of disciplines. The evaluation sought to establish whether (1) use of the framework helped to standardise practice across a range of organisational environments, (2) the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In terms of remaining child-centred, the framework recommends that the person carrying out the assessment must know the child and have a good insight into them as a person beyond their basic needs. Similar to the CAF developed in the UK, the Framework for the Assessment of Vulnerable Children and Their Families: Assessment Tool and Practice Guidance was published in Ireland in 2006 ( Buckley et al ., 2006 ). In this assessment framework, Buckley et al .…”
Section: Reason For the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of remaining child-centred, the framework recommends that the person carrying out the assessment must know the child and have a good insight into them as a person beyond their basic needs. Similar to the CAF developed in the UK, the Framework for the Assessment of Vulnerable Children and Their Families: Assessment Tool and Practice Guidance was published in Ireland in 2006 ( Buckley et al ., 2006 ). In this assessment framework, Buckley et al .…”
Section: Reason For the Studymentioning
confidence: 99%
“…Similar to the CAF developed in the UK, the Framework for the Assessment of Vulnerable Children and Their Families: Assessment Tool and Practice Guidance was published in Ireland in 2006 ( Buckley et al ., 2006 ). In this assessment framework, Buckley et al . (2006) argue that children are not always put at the centre of assessments and social workers do not always engage with them in a meaningful way.…”
Section: Reason For the Studymentioning
confidence: 99%
“…An evaluation in Ireland demonstrated that a nationally developed framework for child protection assessments, to a certain degree, encouraged interdisciplinary and cross-sectoral collaboration (Buckley et al, 2007). This was measured using the following three criteria: (1) whether or not others contributed beyond the one responsible for the case, (2) the number of interdisciplinary meetings and (3) the number of collaborative parties from other services that took part in meetings on the case.…”
Section: Resultsmentioning
confidence: 99%
“…2000; Fernandez & Romeo 2003; Wise 2003; Champion & Burke 2004; Cleaver et al. 2004; Buckley et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In children's services, the focus on identifying and providing services to meet children's needs is evident in countries such as Australia, Canada, Ireland and Sweden (e.g. Jones et al 1998;Kufeldt et al 2000;Fernandez & Romeo 2003;Wise 2003;Champion & Burke 2004;Cleaver et al 2004;Buckley et al 2007). The impetus is hardly surprising.…”
Section: Introductionmentioning
confidence: 99%